Effects of adult Ascaris suum and their antigens (total and trans-cuticular excretory–secretory antigen, cuticular somatic antigen) on intestinal nutrient transport in vivo. Issue 1 (24th January 2023) - Koehler, Sarina; Springer, Andrea; Issel, Nicole; Klinger, Stefanie; Wendt, Michael; Breves, Gerhard; Strube, Christina
Abstract: Abstract: Ascaris suum constitutes a major problem in commercial pig farming worldwide. Lower weight gains in infected pigs probably result from impaired nutrient absorption. This study investigated intestinal nutrient transport in 4 groups of 6 pigs each, which were inoculated with 30 living adult A. suum, or antigen fractions consisting of (1) total excretory–secretory (ES) antigens of adult worms, (2) ES antigens secreted exclusively from the parasites' body surface (trans-cuticular ES) and (3) cuticular somatic antigens of A. suum, compared to placebo-treated controls. Three days after inoculation into the gastrointestinal tract, glucose, alanine and glycyl-l -glutamine transport was measured in the duodenum, jejunum and ileum using Ussing chambers. Transcription of relevant genes [sodium glucose cotransporter 1 (SGLT1), glucose transporter 1 (GLUT1), GLUT2, hypoxia-inducible factor 1-alpha (Hif1 α ), interleukin-4 (IL-4), IL-13, signal transducer and activator of transcription 6 (STAT6), peptide transporter 1 (PepT1)] and expression of transport proteins [SGLT1, phosphorylated SGLT1, GLUT2, Na + /K + -ATPase, amino acid transporter A (ASCT1), PepT1] were studied. Although no significant functional changes were noted after exposure to adult A. suum, a significant downregulation of jejunal GLUT1, STAT6, Hif1 α and PepT1 transcription as well as ileal GLUT2 and PepT1 expression indicates a negative impact of infection on transport physiology. Therefore, the exposure period of 3 days may have been insufficient for functional alterations to become apparent. In contrast, A. suum antigens mainly induced an upregulation of transport processes and an increase in transcription of relevant genes in the duodenum and jejunum, possibly as a compensatory reaction after a transient downregulation. In the ileum, a consistent pattern of downregulation was observed in all inoculated groups, in line with the hypothesis of impaired nutrient transport.